Facile green synthesis of silver nanoparticles decorated on sulfonated graphene oxide by rambutan (Nephelium lappaceum) leaf extract and application as a catalyst for converting benzene into nitrobenzene - Dewi Yuanita Lestari; Akhmad Syoufian; Poedji Loekitowati Hariani; Aldino Javier Saviola; Won-Chun Oh; Amalia Kurnia Amin; Remi Ayu Pratika; Karna Wijaya (Results in Engineering)
Herein, the nitration reaction of benzene over silver nanoparticles (AgNPs) decorated on the surface of sulfonated graphene oxide (SGO) denoted as AgNPs/SGO catalyst has been successfully carried out. AgNPs were synthesized using ethanolic extract of rambutan (Nephelium lappaceum) leaf, which acts as a bio-reductor and capping agent. A modified Hummers method was used to synthesize graphene oxide (GO). The synthesis of sulfonated graphene oxide (SGO) was done by forming aryl diazonium salts. Silver nanoparticles were deposited onto the surface of SGO using the ex-situ method. The average size of AgNPs based on the HR-TEM analysis was 4.235 ± 0.034 nm. Nitration of benzene using the AgNPs/SGO catalyst showed optimal conditions using nitric acid to benzene ratio of 2:1 (v/v) and catalyst weight of 200 mg with nitrobenzene yield and selectivity of 69.95 % and 100 %, respectively. Furthermore, reusability tests of the AgNPs/SGO catalyst demonstrated that after five consecutive runs, the nitrobenzene yield decreased slightly from 69.95 % to 65.81 %, while selectivity remained at 100 %. Thus, this research highlights the potential of this nanocomposite as an effective solid acid catalyst for future application in the green nitrobenzene industry.